EFEKTIVITAS EKSTRAK DAUN SIRIH HUTAN (Piper aduncum L.) DENGAN PELARUT ORGANIK DALAM MENGENDALIKAN ULAT GRAYAK JAGUNG (Spodoptera frugiperda J. E. Smith) DI LABORATORIUM - Dinda Anggraini; Rusli Rustam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Corn (Zea mays L.) is one of the most important food crops in the world after rice and wheat.There were various problem in crop production, one of which is the attack of fall armyworms (Spodoptera frugiperda J. E Smith). The alternative technique to control this was using botanical pesticide from forest betel leaf (Piper aduncum L.). This study aimede to obtain an effective concentration of forest betel leaf extract to control fall armyworm. This research was carried out at the Plant Pests Laboratory of the Faculty of Agriculture and the Laboratory of Natural materials and minerals, Faculty of Engineering, Riau University for 3 months from July to September 2021. The study consisted of six treatments 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1% and four replications This research was arranged by Completely Randomized Design (CRD). The results showed that the use of forest betel leaf extract had a significant effect on the mortality of Spodoptera frugiperda larvaeConcentration of 0.8% is effective in controlling Spodoptera frugiperda larvae because it caused mortality at about 80% with an initial time of death was 1 hour after application and a lethal time of 50 at 13.5 hours after application.